Collective illusions : conformity, complicity, and the science of why we make bad decisions - Rose, Todd, 1974- (Hachette Books, 2022)
The desire to fit in is one of the most powerful, least understood forces in a society. Todd Rose believes that as human beings we continually act against our own best interests out of our brains' misunderstanding of what we think others believe. A complicated set of illusions driven by conformity bias distorts how we see the world around us. From toilet paper shortages to kidneys that get thrown away rather than used for desperately needed organ transplants, from racial segregation to the perceived "electability" of women for political office, from bottled water to "cancel culture," we routinely copy others, lie about what we believe, cling to tribes, and silence others. We are so profoundly social that when we are incongruent with the group that we do lasting damage to our self-worth, diminish our well-being and never realize our full potential. It's why we all too often chase the familiar trappings of money, fame, and success that leave us feeling empty even when we do achieve them. It's why we'll blindly espouse a viewpoint we don't necessarily believe in so that we blend in with the group. We trap ourselves in prisons of our own making that prevent us from living the happy, fulfilled lives we envision. The question is, Why do we keep believing the lies and hurting ourselves? Todd Rose reveals the answer is deeply hard-wired in our DNA, with brains that are more socially dependent than we realize or dare to accept. Most of us would rather be fully in sync with the social norms of our respective groups than true to who we are. Using originally researched data, "Collective Illusions" shows us where we get things wrong and just as important, how we can be authentic in forming our opinions while valuing truth. Rose offers a counterintuitive, empowering, and hopeful explanation for how we can bridge the inference gap, make decisions with a newfound clarity, and achieve fulfillment. Only then can we transform ourselves, and ultimately, society.